Developing Legal Terminology in African Languages as Aid to the Court Interpreter: A South African Perspective - Alberts, Mariëtta; Mollema, Nina (Lexikos, 2013)
The need for unambiguous communication in the theoretical and applied fields of human activity, such as the legal profession, is constantly increasing. Terminologists and subject specialists are focused on the provision of unambiguous source- and target-language terms for well-defined concepts. In order to achieve this aim, it is necessary to determine the precise meanings of terms which enable users to comprehend and use them in a universally accepted manner. Legal language is one of the most difficult languages for special purposes since only legal experts versed in the special vocabulary can communicate successfully — laypeople tend to struggle comprehending the language of law, sometimes called legalese. This study deals with legal language, the bridging of communication problems in a legal setting by especially court interpreters, and difficulties these legal linguists may experience in this endeavour. Some word-forming principles are discussed and examples are given of typical multilingual coinages in the legal profession. Various matters relating to terminology usage in a multilingual society receive attention. Some of the principles of the standardisation, harmonisation and the internationalisation of the terminology of the legal profession are discussed. The research also addresses the work of the Centre for Legal Terminology in African Languages (CLTAL) and of other relevant terminology projects, e.g. that of the Centre for Political and Related Terminology in Southern Africa (CEPTSA).